Evaluation of quizalofop-p-ethyl in cotton and effect on succeeding crop - Hooda, V. S.; Sangwan, Meenakshi; Singh, Samunder; Devi, Sudesh (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif season of 2013 and 2014 to evaluate the bio-efficacy and phytotoxicity of quizalofop-p-ethyl against weeds in cotton. During both the years of study, quizalofop-p-ethyl at 40, 50, 60 & 80 g/ha provided 27 to 60% control of weeds comparative to pendimethalin used at 900 g/ha, however, lower dose of quizalofop-p-ethyl 30g/ha was very poor in controlling the weeds. At 50, 60 and 80 g/ha, quizalofop-p-ethyl did not caused any phytotoxicity in cotton crop and recorded a seed cotton yield which was at par among the treatments of quizalofopp- ethyl at 50, 60 & 80 g/ha which was significantly higher than rest of the treatments except weed free situation. No residual toxicity on succeeding crop of wheat was observed by quizalofop-pethyl application during two years of study.